Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1177/2372732214549328
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Aspects of Contraception, Unintended Pregnancy, and Abortion

Abstract: The knowledge of important biopsychosocial factors linking women's reproductive health and mental health is increasing. This review focuses on psychological aspects of contraception, unintended pregnancy, and abortion because these are common reproductive health experiences in U.S. women's lives. This review addresses the mental-health antecedents and consequences of these experiences, mostly focusing on depression and depressive symptoms before and after unintended pregnancy and contraception. As mental-healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 89 publications
0
42
0
Order By: Relevance
“…A history of depression at baseline was associated with an increased risk of subsequent unplanned pregnancy compared with no history of depression. Although the research regarding the effect of depression on contraceptive use is mixed, Steinberg and Rubin have suggested that because depression affects memory, information‐processing, motivation, and self‐efficacy, it is likely a predictor of behaviors that may lead to unintended pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A history of depression at baseline was associated with an increased risk of subsequent unplanned pregnancy compared with no history of depression. Although the research regarding the effect of depression on contraceptive use is mixed, Steinberg and Rubin have suggested that because depression affects memory, information‐processing, motivation, and self‐efficacy, it is likely a predictor of behaviors that may lead to unintended pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Other variables, such as history of depression and history of abuse, may also be associated with unintended pregnancy and contraceptive use . History of depression was defined as ever being told by a doctor or other health professional that the participant had a depressive disorder.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between induced abortion and mental health is an area of ongoing political and ethical controversy [1]. Many studies found no direct correlation between elective induced abortion and the development of mental consequences, and that the risk of mentalhealth problems is equal whether an unplanned pregnancy is carried to term or terminated with an elective abortion [1,2]. Since the 1973, US Supreme Court decisions legalizing abortions, more than one million abortions have been performed in the United States every year with the vast majority without a necessary medical reason [3].…”
Section: Introductionmentioning
confidence: 99%
“…Detecting and counselling women with psychological symptoms is important. Inconsistency with the use of contraception is increased in these women 5. Reducing the risk of unplanned pregnancies in this group of women through effective contraception is one problem less in their lives.…”
mentioning
confidence: 99%